Measuring handball players trajectories using an automatically trained boosting algorithm - Barros, R. M. L.; Menezes, R. P.; Russomanno, T. G.; Misuta, M. S.; Brandatildeo, B. C.; Figueroa, P. J.; Leite, N. J.; Goldenstein, S. K. (Computer Methods in Biomechanics and Biomedical Engineering, 2011)
The aim of the present paper is to propose and evaluate an automatically trained cascaded boosting detector algorithm based on morphological segmentation for tracking handball players. The proposed method was able to detect correctly 84% of players when applied to the second period of that same game used for training and 74% when applied to a different game. Furthermore, the analysis of the automatic training using boosting detector revealed general results such as the training time initially increased with the number of figures used, but as more figures were added, the training time decreased. Automatic morphological segmentation has shown to be a fast and efficient method for selecting image regions for the boosting detector and allowed an improvement in the automatic tracking of handball players.